Living Ḥadîth Wakaf Menurut Ulama Tradisional dan Modern di Gresik - Abu Azam Al Hadi (Islamica: Jurnal Studi Keislaman, 2014)
This article focuses on the meanings of had?th on waqf according to traditionalist and modern ulama in Gresik, East Java. The signification of Ḥadîth related to religious benefaction (waqf) certainly has various aspects in terms of the social and cultural contexts of the Prophetic traditions. Ḥadîth on waqf has been subject of different meanings reconstruction among Muslim jurists in contemporary context. According to tradisionalist ulama, waqf can be meant as sadaqah jâriyah. They maintain that waqf is turning over properties which have the value of benefit to administrators of waqf who are responsible to maintain the original form of properties. Meanwhile, modern ?ulama argue that waqf is turning over the ?existing? property either eternally or temporally to be used directly and its benefit can be taken continously for the sake of common good or public interest. Waqf is sadaqah jâriyah, the reward of which flows continously. The meaning of ?existing? is that the age of submitted property is determined by its economic value, or as it is written in the statement of waqf. Different meanings of waqf according to traditionalist and modern ?ulama are influenced by their educational backgrounds.